Pengaruh Penempatan dan Pengalaman Kerja Terhadap Kinerja Pegawai pada Dinas Ketahanan Pangan dan Peternakan Provinsi Sumatera Selatan - M Riza Tunase; Mohammad Kurniawan DP; Try Wulandari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to examine the effect of placement and work experience on employee performance at the Food Security and Livestock Service of South Sumatra Province. The research method used was descriptive and verification with a population of 117 respondents. The data collection techniques used were observation, interviews and distributing questionnaires. The data analysis methods used are multiple linear regression, multiple correlation, F test, T test and coefficient of determination. The research results show that placement and work experience have a positive effect on employee performance. Thus, the hypothesis in this research which states that there is an influence of placement and work experience on employee performance can be accepted. It is also hoped that this research can become material for literature on the topic of employee performance.